Analisis Penggunaan E-Learning terhadap Minat Belajar Mahasiswa Program Studi PAI dalam Mata Kuliah Umum Universitas Negeri Padang - Syahrani P, Shancy; Alfurqan, Alfurqan; Hidayat, Ajat (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research was motivated by the occurrence of the Covid 19 pandemic throughout Indonesia which resulted in the educational process in Indonesia being stopped, so that the educational process would not stop, especially Padang State University issuing a policy with the use of E-Learning in the learning process. This study aims to see how the use of E-Learning in the Pancasila Education and Citizenship Education courses and how the interest in learning from PAI students after learning to use the E-Learning. In this study the method used was a qualitative method with a descriptive approach while the technique used for sampling was simple random sampling technique. The source of the data in this study were Islamic Education students class of 2021 with 25 informants. After the research data was processed and the results were obtained that the use of E-Learning in the learning process of Pancasila Education and Citizenship Education ran effectively and efficiently. The thing that attracts the attention of students using E-Learning in their learning process is the design and complete features of E-Learning which make it easier for them in the learning process so that using E-Learning can generate motivation and interest in learning from students after using E-Learning.